Pre-Existing Non-Disabling Encephalomalacia Confers Risk to Stroke Outcomes After Endovascular Treatment - Li, Zibao; Li, Qiang; Ji, Yachen; Chu, Zhaohu; Zhao, Shoucai; Ma, Lingsong; Zhou, Zhiming; Yang, Qian; Huang, Xianjun (Frontiers in Neurology, 2022)
Abstract Background Patients with previous stroke episodes tend to have poor outcomes after endovascular treatment (EVT). Encephalomalacia (EM) is an objective indicator of previous strokes but has not been systematically investigated. The fundamental aim of this exploration is to investigate the effects of pre-existing, non-disabling EM on clinical outcomes after EVT. Methods Consecutive patients undergoing EVT due to anterior circulation large vessel occlusion (LVO) strokes were enrolled in the study. Pre-existing EM was defined as focal hypodense lesions (≥ 3 mm in maximum diameter) on non-contrast cranial CT using axial images before EVT. The primary outcome was 90-day functional assessment using the modified Rankin Scale (mRS) score. The safety outcome was the incidence of symptomatic intracranial hemorrhage (sICH) defined as any hemorrhage within 24 h after EVT, which is responsible for an increase ≥ 4 points in the score of NIHSS. Results Of the 433 patients analyzed in this investigation, pre-existing, non-disabling EM was observed in 106 (24.5%) patients. After adjusting for potential confounding factors, patients with contralateral EM (OR = 2.68, 95% CI = 1.13–6.31; P = 0.025) and with EM+ > 20mm in maximum diameter (OR = 2.21, 95% CI = 1.01–4.85; P = 0.048) were substantially associated with unfavorable outcomes (mRS > 2). For the sICH, we did not observe any association with pre-existing EM (P > 0.05). Conclusions：Pre-existing non-disabling EM is common and safe in patients undergoing EVT. However, contralateral EM and large size of EM may predict an unfavorable outcome at 90 days, which should receive more attention before EVT.